EFFECT OF MATERIAL THICKNESS ON RESIDUAL STRESSES ORIGINATED FROM COOLING PROCESS IN DENTAL RESTORATIONS - Duranay, Mehmet (Turkish Soc Thermal Sciences Technology, 2014)
The main aim of this investigation is to depict the effect of veneering and substrate material thicknesses on the residual stresses occurred on dental restoration after cooling process. The finite element method was used to determine residual stresses distribution on dental restoration. To this end, transient thermal stress analyses were carried out on two-dimensional finite element models during cooling time. It was used dental porcelain and Ni-Cr as veneering and substrate material, respectively. Firstly, cooling curve of dental restoration after firing process was obtained experimentally. Then, to compare experimental and numerical (obtained from the finite element program) cooling curves, an equivalent convection coefficients (Arman vd, 2009) depending on time were defined on the finite element program. The result of the minor revisions on the equivalent convection coefficients, the numerical cooling curve was closed up to experimental cooling curve. ANSYS finite element program was used in the finite element analyses. According to the finite element results, it was seen that residual stresses were significantly affected by the thickness of veneering porcelain and Ni-Cr substrate.
Keywords: Dental restoration; cooling curve; residual stress; finite element analysis